Prediction of COVID-19 Cases in West Nusa Tenggara using SEIQR Model - Gunawan, Lalu Tarangga Arief; Hosea, Albert; Prihantini (Proceeding International Conference on Science and Engineering, 2021)
Abstract. On March 17, 2020 a patient have tested positive for COVID-19. That case become the first confirmed case in the West Nusa Tenggara (NTB), Indonesia. These cases continued to grow over time until September 14, 2020 Which brings the total number of positive cases to 2979.COVID-19 can transmit through direct or indirect contact with infected people’s vomit, urine, feces, or airborne transmission. People who are infected, develop symptoms, or travel between provinces or even countries must be quarantined for 14 days to prevent further spread of COVID-19. A person who survives after quarantine will develop new immune system so that he/she can’t get infected twice. Therefore the appropriate mathematical modeling is SEIQR modeling which stands for susceptible, exposed, symptomatic infected, quarantine, and recover. In this paper, we will conduct SEIQR modeling on COVID-19 in NTB using data obtained from corona.ntbprov.go.id, which is the official website of the government of NTB. From those data, we will obtain the model and also growth chart. The result of our study is growth chart of COVID-19 in NTB.